Diabetic Striate Syndrome: an uncommon complication of diabetes requiring further conceptual expansion - Yu, Ling; Gu, Hua; Hu, Wenli; Yang, Lei (Frontiers in Endocrinology, 2025)
BackgroundDiabetic Striate Syndrome (DSS) is a rare complication of diabetes, clinically characterized by chorea-like involuntary movements and contralateral basal ganglia abnormalities on brain CT and MRI. The identification of atypical DSS cases has broadened our understanding of this complex metabolic disorder.ObjectiveTo investigate the clinical manifestations, imaging features, and potential pathogenesis of DSS to enhance clinical awareness and understanding of the conditionMethodsWe retrospectively analyzed clinical data from eight patients diagnosed with DSS who were hospitalized in the Department of Neurology at Beijing Chaoyang Hospital, affiliated with Capital Medical University, between January 2017 and July 2024. Their clinical presentations and imaging findings were reviewed, and both typical and atypical features, as well as potential pathogenic mechanisms, were discussed in the context of relevant literature.ResultsAmong the eight patients, five were female. All patients had a history of hypertension, and seven had a prior diagnosis of diabetes. Three patients experienced acute or subacute cerebral infarction. Seven patients presented with hemichorea, while one patient exhibited bilateral chorea. Random blood glucose levels at onset ranged from 7.9 to 27.7 mmol/L, and glycated hemoglobin (HbA1c) levels ranged from 8.7% to 15.5%. One patient tested positive for urinary ketones, and one developed symptoms following a rapid drop in blood glucose. Head CT scans revealed high-density lesions in the basal ganglia in four patients. MRI showed T1-weighted hyperintensity in the basal ganglia in seven patients, including one case with bilateral involvement. Hospital stays ranged from 6 to 14 days. All patients showed clinical improvement, with one achieving complete resolution of symptoms. In three cases, symptom improvement was achieved through blood glucose control alone.ConclusionDSS represents a syndrome with an expanding clinical and imaging spectrum as research progresses. In this study, we propose a refined definition of the disorder and reaffirm the hypothesis that both basal ganglia ischemia and hyperglycemia synergistically contribute to the development and progression of DSS.